2013
DOI: 10.1002/pds.3458
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of prescription information in US commercial claims databases

Abstract: Purpose Pharmacy commercial claims databases are widely used for pharmacoepidemiologic research. However, concerns have been raised that these databases may not fully capture claims for generic medication as a result of patients filling outside the context of their insurance. This has implications for many research activities and quality improvement programs. We sought to estimate the percentage of missing drug claims in US commercial claims data using a novel design. Methods Using a large US commercial insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 24 publications
0
69
0
Order By: Relevance
“…23,24 Some warfarin fills may also not be captured due to market influences and cash payments, such as low-cost generic programs in pharmacies. 25,26 The ATRIA score has been used less frequently but has been shown to be better validated in claims data. 9,11 While we could not measure provider preferences directly or cluster by provider, our study sought to disentangle how patient characteristics influenced selection.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Some warfarin fills may also not be captured due to market influences and cash payments, such as low-cost generic programs in pharmacies. 25,26 The ATRIA score has been used less frequently but has been shown to be better validated in claims data. 9,11 While we could not measure provider preferences directly or cluster by provider, our study sought to disentangle how patient characteristics influenced selection.…”
Section: Discussionmentioning
confidence: 99%
“…Warfarin and anti-platelet use was observed to assess switching behaviors. Because warfarin is widely available through low-cost generic programs and may be absent from pharmaceutical claims data, 2224 we considered INR tests during the follow-up period as a proxy for warfarin fills. This methodology has been shown to have high sensitivity and specificity.…”
Section: Methodsmentioning
confidence: 99%
“…19,29 Lauffenburger et al (2013) observed that approximately 10% of individuals with claims for international normalized ratio tests did not have a corresponding prescription claim for warfarin, which is consistent with our observed proportion of LCGP fills for warfarin in the current study. 30 We expanded on the previous studies of LCGP use by considering demographic and clinical characteristics, trend of LCGP use over time, and the specific medication classes filled through these programs. 19,29 Zhang et al (2012) evaluated LCGP use in Medicare Part D claims in 2008 and found that about 16% of beneficiaries used a $4 generic medication.…”
Section: Discussionmentioning
confidence: 99%